Monoolein-based cubosomes affect lipid profile in HeLa cells. (October 2015) - Rosa, Antonella; Murgia, Sergio; Putzu, Danilo; Meli, Valeria; Falchi, Angela Maria
Graphical abstract: Highlights: We explored lipid changes in HeLa cells treated (2 and 4 h) with monoolein-based cubosomes stabilized by Pluronic F108. A significant increase of oleic acid was observed in treated cells after lipid component saponification. Nanoparticle uptake modulated cell lipids, with an incorporation of oleic acid in HeLa phospholipids and triacylglycerols. Increased amount of intracellular membranes and lipid droplets was detected by an alternative Nile red staining technique. Abstract: Monoolein-based cubosomes are promising drug delivery nanocarriers for theranostic purposes. Nevertheless, a small amount of research has been undertaken to investigate the impact of these biocompatible nanoparticles on cell lipid profile. The purpose of the present investigation was to explore changes in lipid components occurring in human carcinoma HeLa cells when exposed to short-term treatments (2 and 4 h) with monoolein-based cubosomes stabilized by Pluronic F108 (MO/PF108). A combination of TLC and reversed-phase HPLC with DAD and ELSD detection was performed to analyze cell total fatty acid profile and levels of phospholipids, free cholesterol, triacylglycerols, and cholesteryl esters. The treatments with MO/PF108 cubosomes, at non-cytotoxic concentration (83 μg/mL of MO), affected HeLa fatty acid profile, and a significant increase in the level of oleic acid 18:1 n -9 was observed in treated cells after lipid component saponification. Nanoparticle uptake modulated HeLa cell lipid composition, inducing a remarkable incorporation of oleic acid in the phospholipid and triacylglycerol fractions, whereas no changes were observed in the cellular levels of free cholesterol and cholesteryl oleate. Moreover, cell-based fluorescent measurements of intracellular membranes and lipid droplet content were assessed on cubosome-treated cells with an alternative technique using Nile red staining. A significant increase in the amount of the intracellular membranes and mostly in the cytoplasmic lipid droplets was detected, confirming that monoolein-based cubosome treatment influences the synthesis of intracellular membranes and accumulation of lipid droplets.